2020
DOI: 10.1002/aenm.201902662
|View full text |Cite
|
Sign up to set email alerts
|

Nonaromatic Green‐Solvent‐Processable, Dopant‐Free, and Lead‐Capturable Hole Transport Polymers in Perovskite Solar Cells with High Efficiency

Abstract: With the recent developments in the efficiency of perovskite solar cells (PSCs), diverse functionalities are necessary for next‐generation charge‐transport layers. Specifically, the hole‐transport layer (HTL) in the various synthesized materials modified with functional groups is explored. A novel donor–acceptor type polymer, alkoxy‐PTEG, composed of benzo[1,2‐b:4,5:b′]dithiophene and tetraethylene glycol (TEG)‐substituted 2,1,3‐benzothiadiazole is reported. The alkoxy‐PTEG exhibits high solubility even in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
124
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 51 publications
0
124
0
2
Order By: Relevance
“…
junction devices. [4][5][6][7][8][9][10] Compared to traditional solar cells, PSCs have high stability, high efficiency, low cost, and simple structure. PSCs have two iconic structures: mesoporous and planar structures.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
junction devices. [4][5][6][7][8][9][10] Compared to traditional solar cells, PSCs have high stability, high efficiency, low cost, and simple structure. PSCs have two iconic structures: mesoporous and planar structures.
…”
mentioning
confidence: 99%
“…PSCs have two iconic structures: mesoporous and planar structures. [9,11] The planar structure has been widely used because it has high PCE and simple preparation process; new attempts and changes have been made continuously to optimize its performance. [12][13][14][15][16] Improving the performance of planar PSCs is critically dependent on the properties of both their perovskite active layers and interfaces.…”
mentioning
confidence: 99%
“…Reproduced with permission. [ 20 ] Copyright 2020, WILEY‐VCH Verlag GmbH & Co. KgaA. d) The PL spectrum of glass/CB‐perovskite, glass/EA‐perovskite, glass/CB‐perovskite/Spiro‐OMeTAD, glass/EA‐perovskite/Spiro‐OMeTAD.…”
Section: Precursor Solventsmentioning
confidence: 99%
“…2,2′,7,7′‐tetrakis( N,N ‐di‐pmethoxyphenylamine)‐9,9′‐spirobifluorene (Spiro‐OMeTAD) is the most commonly used HTM in PSCs, but it can be dissolved only in halogenous or toxic solvent such CB, dichlorobenzene (DCB), and toluene. [ 20 ] The calculated Hansen solubility in Figure 3b indicated that uniting alkoxy side chains and tetraethylene glycol side chains is suitable for green preparation process due to superior solubility capacity ( R 0 ). Furthermore, the alkoxy chains have strong interaction with Pb 2+ with the binding constant of 2.76 m −1 (Figure 3c), which indicated excellent ability of coordination with Pb 2+ .…”
Section: Etm/htm Solventsmentioning
confidence: 99%
“…There are very few reports regarding HTMs processed in nonhalogenated solvents. 24 28 Nevertheless, in all the reported examples, the HTMs were mostly synthesized in modest overall yields via onerous multistep syntheses employing costly and toxic palladium catalysts and were purified via stringent and long procedures that limit their scalability. 24 28 Thus, HTMs that combine green solvents processability with cost-effective and eco-friendly synthesis and purification are still lacking.…”
Section: Introductionmentioning
confidence: 99%